2022
DOI: 10.1158/1535-7163.mct-21-0726
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 Specific CAR T Cells for the Naturally Occurring, Spontaneous Canine Sarcoma Model

Abstract: One obstacle for human solid tumor immunotherapy research is the lack of clinically relevant animal models. In this study, we sought to establish a CAR T cell treatment model for naturally occurring canine sarcomas as a model for human CAR T cell therapy. Canine CARs specific for B7-H3 were constructed using a single chain variable fragment derived from the human B7-H3-specific antibody MGA271, which we confirmed to be cross-reactive with canine B7-H3. After refining activation, transduction and expansion meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“… 65 , 66 , 67 Dogs bearing sarcomas have also been treated with B7-H3 CAR-T cells, which are also in human clinical trials ( NCT046670068 ), demonstrating feasibility and safety. 68 Many of the observations made in human CAR-T cells trials have been recapitulated in dogs, including the development of cytokine release syndrome, the emergence of antigen-negative tumor relapse, and the development of anti-mouse antibodies generated against the murine portion of the scFv used in many human and dog CAR constructs ( Figure 2 ). 69 While thus far use of the canine CAR-T cell models and clinical utilization by veterinarians is lagging behind, canine models can serve as a promising translational bridge, and activity in this area is increasing.…”
Section: Studying Efficacy Of Car-t Cells In Animal Modelsmentioning
confidence: 99%
“… 65 , 66 , 67 Dogs bearing sarcomas have also been treated with B7-H3 CAR-T cells, which are also in human clinical trials ( NCT046670068 ), demonstrating feasibility and safety. 68 Many of the observations made in human CAR-T cells trials have been recapitulated in dogs, including the development of cytokine release syndrome, the emergence of antigen-negative tumor relapse, and the development of anti-mouse antibodies generated against the murine portion of the scFv used in many human and dog CAR constructs ( Figure 2 ). 69 While thus far use of the canine CAR-T cell models and clinical utilization by veterinarians is lagging behind, canine models can serve as a promising translational bridge, and activity in this area is increasing.…”
Section: Studying Efficacy Of Car-t Cells In Animal Modelsmentioning
confidence: 99%
“…Although clinical veterinary studies are still in the beginning phases, the potential for breakthrough therapies, like has happened for human hematologic oncology, is high. Veterinary clinical trials involving infusions of T cells and NK cells have demonstrated the feasibility and safety of harvesting and manufacturing cells for clinical use (30,78,83,98). However, to fully break into the cellular immunotherapy sector the way human medicine has, veterinary schools or other hospitals will need appropriate infrastructure for cellular manufacturing and genetic modification, or identify industry partners.…”
Section: Discussionmentioning
confidence: 99%
“…References cells (82) were more cytotoxic than HER2 CAR T cells toward canine osteosarcoma spheroids, but cytotoxicity was similar for the constructs incorporating CD28 or 4-1BB signaling domains (83). Two healthy canine subjects were then infused with either frozen or fresh autologous B7-H3 CAR T cells.…”
Section: Feline Phenotypic Markersmentioning
confidence: 99%
“…In comparative oncology that studies animal tumor models that develop cancers spontaneously, pet dog models are gaining significant attraction as they are one step closer to real world cancers given not only clinical and molecular similarities but also patient heterogeneity. A number of trials using different immunotherapy approaches—including CAR T cells—are used to treat HER2+ osteosarcoma, B7-H3+ sarcomas, and gliomas [ 4 , 219 ]. However, the paucity of patient recruitment similarly seen in human trials might need more expeditious cancer models.…”
Section: Preclinical Models For Trafficking and Infiltrationmentioning
confidence: 99%